‘Evidence’ of Neglect as a Form of Structural Violence: Parents with Intellectual Disabilities and Custody Deprivation - Sigurjónsdóttir, Hanna Björg; Rice, James G. (Social Inclusion, 2018)
This contribution draws upon the findings from a multi-year project in Iceland entitled Family Life and Disability. One goal of the project was to analyse whether or not parents with intellectual disabilities (ID) experienced differential treatment in custody deprivation proceedings. The dataset consisted of the analysis of publicly available court documents concerning custody deprivation cases from 2012 to 2017. The project later expanded its dataset to include supplementary information provided by parents. The initial findings mirrored that of the international literature, that parents with ID faced disproportionate levels of permanent custody deprivation and prejudicial attitudes from the child protection system. This contribution critically explores the evidence of parenting neglect that forms of basis for custody deprivation in our dataset. Both authors noted a preponderance of evidence in our dataset that appeared strange and at times absurd, and generally did not appear in cases were ID was not a factor. We contend that this evidence played a prejudicial role in the outcome of these cases. In conclusion we argue that the patterned reliance upon this kind of ‘evidence’ is a form of structural violence which serves to unjustly exclude marginalised groups from the parenting role.